2013
DOI: 10.1176/appi.ajp.2013.13020214
|View full text |Cite
|
Sign up to set email alerts
|

Assisting Social Security Disability Insurance Beneficiaries With Schizophrenia, Bipolar Disorder, or Major Depression in Returning to Work

Abstract: Implementation of the complex intervention in routine mental health treatment settings was feasible, and the intervention was effective in assisting individuals disabled by schizophrenia or depression to return to work and improve their mental health and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 25 publications
6
75
1
1
Order By: Relevance
“…It is being argued that stress related to new and challenging experience may lead to deterioration of individuals' mental health. Individual Placement and Support studies consistently reported positive findings which showed lower risk of hospitalization, enhanced mental health status, and life satisfaction in IPS participants while compared to vocational service users [33]. Participants of the experimental group also presented significantly greater decrease in depression than non-working subjects [34].…”
Section: Individual Placement and Support Program And Recoverymentioning
confidence: 85%
“…It is being argued that stress related to new and challenging experience may lead to deterioration of individuals' mental health. Individual Placement and Support studies consistently reported positive findings which showed lower risk of hospitalization, enhanced mental health status, and life satisfaction in IPS participants while compared to vocational service users [33]. Participants of the experimental group also presented significantly greater decrease in depression than non-working subjects [34].…”
Section: Individual Placement and Support Program And Recoverymentioning
confidence: 85%
“…Recent studies have shown that low income in the general population is associated with greater mortality and poorer health (30), and the modest income supplements and health benefits provided by SSA disability programs may be important contributors to survival for young people with first-episode psychosis. Even though programs with a specialized focus on rehabilitation clearly generate significant improvements in employment (31,32), economic selfsufficiency is rarely attained (33).…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous efforts to engage in QI focused on supported employment. Some have been highly effective, while others have been frustrated, mostly by organizational or fi nancial constraints (Drake et al, 2013;Frey et al, 2008Frey et al, , 2011Hamilton et al, 2013 ;McHugo et al, 2007 ).…”
Section: Quality Improvement For Evidence-based Practicesmentioning
confidence: 99%